Climate Variability and Soil Nutrients Status along Altitudinal Gradient in Kigezi Highlands, Southwestern Uganda - Twagiramaria, Fortunate; Tolo, Casim Umba (Scientific Research, 2016)
Kigezi highlands currently experiences changes in precipitation and temperature which modify the evaporation and soil moisture storage leading to alterations in runoff and other components of hydrological systems. Extreme events, like floods and droughts, are more intense and frequent. Furthermore, heavy unpredictable rainfall has become frequent in the area, causing soil erosion and floods that destroy crops. Soil erosion is particularly a pressing challenge due to steep-sided hills leading to deterioration of soil nutrients including soil fertility. The unpredictable rains and droughts are attributed to climate change and variability. Consequently, climate change and variability have caused a significant impact on soil nutrients which have affected the agricultural productivity in the area. This paper presents findings of empirical study which explored the climate variability and soil nutrient status along altitudinal gradient. The paper particularly addresses key questions of: land management practices in the study area, nutrient availability and their effects on productivity of selected crops along altitudinal gradient in changing climate and variability. Independent variables such as topographic sequence along altitudinal gradient were evaluated against dependent variables such as yield harvests of selected grown crops and soil nutrients. Samples for crop yields were collected along transect of 0.5 kilometer using a quadrant of 4 × 4 m2 along attitudinal gradient. Soil samples were taken from selected plots at 0-20cm soil depth for nutrient analysis. Analysis of physical and chemical soil parameters was carried out on soil samples and these include: soil pH, soil organic content, total nitrogen, available soil phosphorous and exchangeable bases (Ca, Mg, K and Na). The study showed that middle parts of the transects had the highest concentration of most soil nutrients, probably because the middle parts could have been a deposition centre for some organic matter from the upper parts of the hills, and lower lying areas were being affected by floods that affects the decomposition of organic matter which is the main source of nutrients. Similarly, the middle parts of the study were the most fertile due to the high concentration of soil nutrient compositions. This indicates that crop yields were significantly affected by availability of soil nutrients along same gradient, attributable to the severity in soil erosion, nutrients leaching and farming practices.
Keywords: Climate Change; Climate Variability; Soil Nutrients; Kigezi Highlands; Altitudinal Gradient; Southwestern Uganda